Learning History Outside The Classroom: Observation-Based Learning Strategies and Hands-on Field Experiences for High School Students - Uddin, Ahmad Rofi; Widiadi, Aditya Nugroho; Jauhari, Najib (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
The primary issue in the realm of history education in secondary schools pertains to the dearth of student engagement, largely attributable to the conventional pedagogical methods that are characterized by monotony and a paucity of contextual relevance. The present study examines the effectiveness of outdoor learning-based history learning strategies through on-site and experience vibes approaches at cultural sites in Singosari District, Malang Regency. The objective of the present study was to evaluate the impact of outdoor learning on historical understanding, learning interest, and awareness of cultural and environmental values. The present study employed a mixed methods intervention design approach, which integrates quantitative and qualitative methods in a cohesive manner. The population under study comprised all grade X students of SMAN 1 Purwosari, with a total population of approximately 400 students, of which a sample of 183 students was selected through purposive sampling. Quantitative data were collected through the administration of pre- and post-activity questionnaires, while qualitative data were obtained through open interviews, activity documentation, and analysis of student impressions and messages. Quantitative data were analyzed using the percentage change in the results of the pre-post questionnaire, while qualitative data were analyzed thematically to reveal the meaning of students' experiences during the activity. The findings indicated a substantial enhancement in historical comprehension, a marked increase in enthusiasm for learning, and a notable development in empathy for cultural heritage and the environment. A substantial majority of students reported that the activities were both enjoyable and beneficial, with an overwhelming 99.1% expressing a profound experience. The findings of this study demonstrate the efficacy of the direct experience-based history learning model in fostering reflective, participatory, and contextual learning. Furthermore, the model's relevance to the implementation of the Merdeka Curriculum at various levels of education is substantiated.Keywords: Outdoor Learning, Learning Strategy, on-site observation, experience vibes dan Situs-Situs Singosari